Theory of Leadership Styles in The Concept of Islamic Education Management - Iqbal, Teguh; Oktaviani, Eka Tri; Vista, Aura; Haryanti, Erni (Universitas Negeri Jakarta, 2024)
Background Ideally, a leader should possess good management skills, as success or failure depends on leadership, thus requiring the necessary skills to achieve the goals and aspirations of the organization. Purpose The purpose of this journal is to explore leadership theories and how Islamic educational management perspectives relate to leadership styles. Design/method/approach This research uses a literature study method by reviewing various journals, books, and previous research results relevant to this discussion. Results It can be found that there is a wide range of theories related to leadership, with each theory offering its own perspective to explain the concept of leadership styles. In the context of Islamic educational management, leadership styles are also a key point of discussion, particularly in their implementation in schools and institutions. Islamic educational management plays an important role in leadership styles, which can be adapted to different situations and conditions. Contribution/value The use of leadership styles will significantly determine the effectiveness of an organization in achieving its goals.